The Relationship Between Vitamin D and Postoperative Atrial Fibrillation: A Prospective Cohort Study - Ohlrogge, Amelie H.; Brederecke, Jan; Ojeda, Francisco M.; Pecha, Simon; Börschel, Christin S.; Conradi, Lenard; Rimkus, Vanessa; Blankenberg, Stefan; Zeller, Tanja; Schnabel, Renate B. (Frontiers in Nutrition, 2022)
Background and aims The relationship between postoperative atrial fibrillation (POAF) and 25-hydroxyvitamin D (25(OH)D) concentration as well as vitamin D supplementation has been discussed controversially. The relation of pre-operative vitamin D status and POAF remains unclear. Methods and results We analysed the risk of POAF in a prospective, observational cohort study of n=199 patients undergoing coronary artery bypass graft surgery (CABG) with 25(OH)D concentration. The mean age ± standard deviation was 66.8 years, 15.6% were women. The median (25th/75th percentile) vitamin D concentration at baseline was 17.7 (12.6/23.8) ng/l. During follow-up we observed 50 cases of POAF. In age, sex and creatinine-adjusted analyses, 25(OH)D was associated with an increased risk of POAF, though with borderline statistical significance (odds ratio (OR) 2.04, 95% confidence interval (CI) 0.96 to 4.32, p value 0.064), in further risk factor-adjusted analyses the results remained stable (OR 2.10, 95% CI 0.95 to 4.63, p value 0.067). The subgroup with vitamin D supplementation showed an increased risk of POAF (OR 4.69 (95% CI 1.05 to 20.94, p value 0.043). Conclusion In our contemporary mid-European cohort, higher 25(OH)D concentration did not show a benefit for POAF in CABG patients and may even be harmful, though with borderline statistical significance. Our data are in line with a recent randomized study in community-based adults and call for further research to determine both, the clinical impact of elevated 25(OH)D concentration and vitamin D supplementation as well as the possible underlying pathophysiological mechanisms.